Matematika/Sinuso Integralas: Skirtumas tarp puslapio versijų

:<math>=-\frac{e^{-x\cdot\infty}(x\sin(\infty)+\cos(\infty))}{x^2+1} -\left(-\frac{e^{-x\cdot 0}(x\sin(0)+\cos(0))}{x^2+1}\right)=</math>
:<math>=-\frac{e^{-x\cdot\infty}(x\sin(\infty)+\cos(\infty))}{x^2+1} +\frac{e^0 (x\cdot 0+1)}{x^2+1}=</math>
:<math>=-\frac{e^{-x\cdot\infty}(x\sin(\infty)+\cos(\infty))}{x^2+1} +\frac{1\cdot (0+1)}{x^2+1}=</math>
:<math>=-\frac{e^{-x\cdot\infty}(x\sin(\infty)+\cos(\infty))}{x^2+1} +\frac{1}{x^2+1}=</math>
 
==Nuorodos==
5 067

pakeitimai